Let’s Play GOLF! Or, the Free Will Defense Is Dead - Cowan, Steven B. (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
A central feature of the “free will defense” as developed by Alvin Plantinga is his response to the claim that God can create a world containing creatures with libertarian freedom that contains no moral evil. Plantinga’s response appeals to the notion of “morally significant freedom” according to which free creatures, in order to do moral good, must be capable of moral evil. In this paper, I argue, first, that morally significant freedom is not required for free creatures to do moral good and, second, that other recent attempts to necessitate a creaturely capability for evil likewise fail. The upshot of my paper is that the free will defense simply won’t work because it is possible and feasible for God to create a world containing libertarianly free creatures capable of moral good and yet containing no moral evil.